RETRACTION NOTE: Effects of gallic acid on rat testopathy following morphine administration: an experimental study - Cyrus Jalili; Amir Abdolmaleki; Shiva Roshankhah; Mohammad Reza Salahshoor (Shahrekord University of Medical Sciences, 2022)
This paper was published in the Journal of Herbmed Pharmacology in 2020 (doi: 10.15171/jhp.2020.09) (1). Based on an email received from the team of young researchers recently, we were informed that this published paper presented some data as same as data presented in two other published papers (2,3), which are considered as ethical misconduct. This issue was investigated by the editorial team of the Journal of Herbmed Pharmacology. As a result, based on the Committee on Publication Ethics (COPE) guidelines, the editors decided to retract this paper. The authors were informed and advised on this serious ethical breach. This article has been retracted at the request of the corresponding author. Given that both studies on hepatotoxicity were performed and published by the authors at the same time. Some data and Excel files were inadvertently moved from the first article (Determination of histopathological and biomedical parameters in protective effects of Petroselinum crispum on hepatotoxicity induced by dichlorvos in male Wistar rats) to the second article (Histopathological and biomedical parameters determination in the protective effect of crocin on hepatotoxicity induced by methotrexate in rats) and caused the similarity of figures 1, 2 and 5 in the two articles. The retracted article will remain online to maintain the scholarly record, but it will be watermarked on each page as 'retracted'. References 1. Jalili C, Abdolmaleki A, Roshankhah SH, Salahshoor MR. Effects of gallic acid on rat testopathy following morphine administration: an experimental study. J Herbmed Pharmacol. 2020;9(1):61-67. doi: 10.15171/jhp.2020.09. 2. Salahshoor MR, Faramarzi A, Roshankhah S, Jalili C. The protective effect of Pentoxifylline on testopathy in male rats following Dimethyl Nitrosamine administration: An experimental study. Int J Reprod BioMed. 2019;17(10):727-38. 3. Salahshoor MR, Abdolmaleki A, Jalili C, Roshankhah S. Can pentoxifylline recover reproductive parameters' damage induced by high-protein diet in male rats? Advances in Human Biology. 2019;9(3):203-9.